A general spectrum model for X-ray generators. (April 2016) - Deresch, A.; Bellon, C.; Jaenisch, G.-R.
Abstract: A fast quantitative model for the energy spectra of radiation emitted by X-ray tubes is described, handling thin as well as thick plane targets of arbitrary materials. The developed model is based on fundamental interaction cross sections, describing electron and photon transport via numerical integration of discretized distributions. While the focus lies on bremsstrahlung production, modeling of characteristic radiation is fully integrated. The model does not include any free parameters. The validity of the model is shown through comparison with measurements and Monte Carlo simulations for several combinations of target material and acceleration potential between 30 kV and 450 kV.